PENDAMPINGAN PEDAGANG PENGECER AYAM POTONG “IBU JUNI” DI DESA BANYUNING DALAM MENINGKATKAN USAHA DI ERA SOCIETY 5.0 - Putu Eka Nopiyani; Riana Dewi Kartika; Komang Rahayu Widiastini (Penerbit Widina, Widina Media Utama, 2023)
The purpose of this community service is to increase sales of broiler meat, internet marketing-based sales and increase knowledge in the financial sector for the